1999
DOI: 10.1093/emboj/18.18.4969
|View full text |Cite
|
Sign up to set email alerts
|

The p38 MAP kinase pathway signals for cytokine-induced mRNA stabilization via MAP kinase-activated protein kinase 2 and an AU-rich region-targeted mechanism

Abstract: R.Winzen and M.Kracht contributed equally to this workStabilization of mRNAs contributes to the strong and rapid induction of genes in the inflammatory response. The signaling mechanisms involved were investigated using a tetracycline-controlled expression system to determine the half-lives of interleukin (IL)-6 and IL-8 mRNAs. Transcript stability was low in untreated HeLa cells, but increased in cells expressing a constitutively active form of the MAP kinase kinase kinase MEKK1. Destabilization and signal-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
644
4
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 727 publications
(683 citation statements)
references
References 88 publications
28
644
4
5
Order By: Relevance
“…We found that the p38 selective inhibitor SB203580 suppressed IGF-I-induced activation of COX-2 promoter activity and mRNA stabilization. This is consistent with previous findings showing that p38 MAPK was involved in COX-2 transcription presumably through increasing AP-1 activity (41,(45)(46)(47), and that p38 MAPK regulated COX-2 mRNA stabilization by its downstream kinase MK-2 (9,36,48).…”
Section: Discussionsupporting
confidence: 93%
“…We found that the p38 selective inhibitor SB203580 suppressed IGF-I-induced activation of COX-2 promoter activity and mRNA stabilization. This is consistent with previous findings showing that p38 MAPK was involved in COX-2 transcription presumably through increasing AP-1 activity (41,(45)(46)(47), and that p38 MAPK regulated COX-2 mRNA stabilization by its downstream kinase MK-2 (9,36,48).…”
Section: Discussionsupporting
confidence: 93%
“…Several examples point to stabilization of otherwise labile mRNAs under conditions promoting induction, which contributes to a rapid increase in their amounts. Phorbol ester treatment increased the half-life of GM-CSF mRNA (Shaw and Kamen, 1986;Bickel et al, 1990); stabilization of mRNAs also contributes to the strong and rapid induction of genes in the inflammatory response (Winzen et al, 1999); and activation of the leukocyte integrin lymphocyte-function-associated antigen-1 (LFA-1) promotes the induction of urokinase plasminogen activator receptor in the T-cell membrane through the stabilization of its ARE-containing mRNA (Wang et al, 1998).…”
Section: Are-mediated Stabilization Of Mrnamentioning
confidence: 99%
“…The affinity of recombinant p37 AUF1 for the ARE motif is closely correlated with its potential to destabilize the mRNA . Inhibition of the p38 pathway stabilizes the AREcontaining mRNAs (Winzen et al, 1999;Lasa et al, 2000), inactivating AUF1 protein (Sirenko et al, 1997), which suggests that p38 is involved in the AUF1 activity. In conclusion, the efficiency of ARE-dependent mRNA turnover is compromised in cells containing low levels of endogenous p37 AUF1 and p40 AUF1 (Ross et al, 1991;Buzby et al, 1996) or following sequestration of AUF1 by treatment with hemin (Loflin et al, 1999).…”
Section: Auf1mentioning
confidence: 99%
“…Our results show that AgC10 destabilizes TNF and COX-2 mRNA by inhibiting activation of p38 mitogen-activated protein kinase (MAPK) and its substrate MAPK-activated protein kinase-2 (MAPKAP-K2). Macrophage stimulation with LPS activates these kinases, which have been previously described as important regulators of TNF and COX-2 mRNA stability [15,16]. These results represent a previously undescribed mechanism in which a parasite surface molecule is able to avoid the release of proinflammatory mediators that play a crucial role in the elimination of T. cruzi.…”
Section: Introductionmentioning
confidence: 89%
“…In turn, p38 phosphorylates and activates MAPKAP-K2 [20]. This signal transduction cascade is required for the expression of several proinflammatory genes, including TNF and COX-2, and exerts its effects, at least in part, through mRNA stability [15,16]. To test if AgC10 affects p38 activation, we performed Western blot analysis of activated macrophages using anti-phosphorylated p38 antibody that recognizes the phosphorylated and active forms of this kinase.…”
Section: Agc10 Inhibits P38 and Mapkap-k2 Activationmentioning
confidence: 99%